(untitled) (The Review of Diabetic Studies, 2024)
Cancer and its treatment are commonly linked to immune dysfunction, malnutrition and increased vulnerability to infection, which can negatively affect treatment tolerance and clinical outcome. There is increasing evidence that immunonutrition, meaning targeted nutritional strategies to modulate immune responses, plays a critical role in improving therapeutic efficacy and quality of life in cancer patients. Diet, bioactive phytochemicals and medicinal herbs have received greater attention for their immunomodulatory, anti-inflammatory and antioxidant properties, especially as adjuncts to conventional cancer therapies such as chemotherapy and radiotherapy. This review critically examines the role of immunonutrition in the context of cancer patients with a special emphasis on the impact of dietary constituents, plant-based phytochemicals and traditional Indian medicinal herbs in modulating immune function and treatment outcomes. A systematic narrative review was conducted using electronic databases such as PubMed, Scopus, Web of Science, and Google Scholar, encompassing pertinent experimental, clinical, and review articles published between 2000 and 2025. We discuss important immunonutrients like arginine, glutamine, omega-3 fatty acids, vitamins and trace elements and major phytochemicals like curcumin, resveratrol, epigallocatechin gallate and quercetin. Furthermore, the evidence for immunomodulatory potential of traditional Indian herbs like Tinospora cordifolia, Withania Somnifera, Curcuma longa and Ocimum sanctum is systematically summarized. The results indicate that immunonutrition might improve immune competence, reduce treatment-related toxicities, improve inflammatory and haematological parameters and increase overall treatment tolerance in cancer patients. However, heterogeneity of study designs, lack of large scale randomized clinical trials and concerns regarding standardization and herb–drug interactions are still significant challenges. In conclusion, immunonutrition is a promising supportive modality in integrative oncology, with a need for further well-designed clinical studies to establish standardized protocols and evidence-based guidelines for its safe and effective use in cancer care.